The mandible and dentition of the Early Cretaceous monotreme Teinolophos trusleri. Issue 4 (1st October 2016) - Rich, Thomas H.; Hopson, James A.; Gill, Pamela G.; Trusler, Peter; Rogers-Davidson, Sally; Morton, Steve; Cifelli, Richard L.; Pickering, David; Kool, Lesley; Siu, Karen; Burgmann, Flame A.; Senden, Tim; et al.
Abstract : Rich, T.H., Hopson, J.A., Gill, P.G., Trusler, P., Rogers -Davidson, S., Morton, S., Cifelli, R.L., Pickering, D., Kool, L., Siu, K., Burgmann, F.A., Senden, T., Evans, A.R., Wagstaff, B.E., Seegets -Villiers, D., Corfe, I.J., Flannery, T.F., Walker, K., Musser, A.M., Archer, M., Pian, R. & Vickers -Rich, P., June 2016. The mandible and dentition of the Early Cretaceous monotreme Teinolophos trusleri . Alcheringa 40, xx–xx. ISSN 0311-5518. The monotreme Teinolophos trusleri Rich, Vickers-Rich, Constantine, Flannery, Kool & van Klaveren, 1999 from the Early Cretaceous of Australia is redescribed and reinterpreted here in light of additional specimens of that species and compared with the exquisitely preserved Early Cretaceous mammals from Liaoning Province, China. Together, this material indicates that although T. trusleri lacked a rod of postdentary bones contacting the dentary, as occurs in non-mammalian cynodonts and basal mammaliaforms, it did not share the condition present in all living mammals, including monotremes, of having the three auditory ossicles, which directly connect the tympanic membrane to the fenestra ovalis, being freely suspended within the middle ear cavity. Rather, T. trusleri appears to have had an intermediate condition, present in some Early Cretaceous mammals from Liaoning, in which the postdentary bones cum ear ossicles retained a connection to a persisting Meckel's cartilage although not to the dentary. Teinolophos thus indicates that the condition of freely suspended auditory ossicles was acquired independently in monotremes and therian mammals. Much of the anterior region of the lower jaw of Teinolophos is now known, along with an isolated upper ultimate premolar. The previously unknown anterior region of the jaw is elongated and delicate as in extant monotremes, but differs in having at least seven antemolar teeth, which are separated by distinct diastemata. The dental formula of the lower jaw of Teinolophos trusleri as now known is i2 c1 p4 m5. Both the deep lower jaw and the long-rooted upper premolar indicate that Teinolophos, unlike undoubted ornithorhynchids (including the extinct Obdurodon ), lacked a bill. Thomas H. Rich [ trich@museum.vic.gov.au ], Sally Rogers-Davidson [ srogers@museum.vic.gov.au ], David Pickering [ dpick@museum.vic.gov.au ], Timothy F. Flannery [ tim.flannery@textpublishing.com.au ], Ken Walker [ kwalker@museum.vic.gov.au ], Museum Victoria, PO Box 666, Melbourne, Victoria 3001, Australia; James A. Hopson [ jhopson@uchicago.edu ], Department of Organismal Biology & Anatomy, University of Chicago, 1025 East 57th Street, Chicago, IL 60637, USA; Pamela G. Gill [ pam.gill@bristol.ac.uk ], School of Earth Sciences, University of Bristol, Bristol BS8 1RJ, U.K. and Earth Science Department, The Natural History Museum, Cromwell Road, London SW7 5BD, UK; Peter Trusler [ peter@petertrusler.com.au ], Lesley Kool [ koollesley@gmail.com ], Doris Seegets-Villiers [ doris.seegets-villiers@monash.edu ], Patricia Vickers-Rich [ pat.rich@monash.edu ], School of Earth, Atmosphere and Environment, Monash University, Victoria 3800, Australia; Steve Morton [ steve.morton@monash.edu ], Karen Siu [ karen.siu@monash.edu ], School of Physics and Astronomy, Monash University, Victoria 3800, Australia; Richard L. Cifelli [ rlc@ou.edu ] Sam Noble Oklahoma Museum of Natural History, University of Oklahoma, Norman, OK 73072, USA; Flame A. Burgmann [ flame.burgmann@monash.edu ], Monash Centre for Electron Microscopy, 10 Innovation Walk, Monash University, Clayton, Victoria 3800, Australia; Tim Senden [ Tim.Senden@anu.edu.au ], Department of Applied Mathematics, Research School of Physical Sciences and Engineering, The Australian National University, Canberra, Australian Capital Territory 0200, Australia; Alistair R. Evans [ alistair.evans@monash.edu ], School of Biological Sciences, Monash University, Victoria 3800, Australia; Barbara E. Wagstaff [ wagstaff@unimelb.edu.au ], School of Earth Sciences, The University of Melbourne, Victoria 3010, Australia; Ian J. Corfe [ ian.corfe@helsinki.fi ], Institute of Biotechnology, Viikinkaari 9, 00014, University of Helsinki, Finland; Anne M. Musser [ anne.musser@austmus.gov.au ], Australian Museum, 1 College Street, Sydney NSW 2010 Australia; Michael Archer [ m.archer@unsw.edu.au ], School of Biological, Earth, and Environmental Sciences, University of New South Wales, Sydney, NSW 2052, Australia; Rebecca Pian [ rpian@amnh.org ], Division of Paleontology, American Museum of Natural History, Central Park West at 79th Street, New York, NY 10024-5192, USA. Received 7.4.2016; accepted 14.4.2016.